N2: reading, writing, walking the South African highway. (2nd January 2017) - Twidle, Hedley
Abstract: This piece is drawn from a larger project that asks what it might mean to write a cultural history or "biography" of the longest highway in South Africa, the N2. Influenced by literature on the everyday, on infrastructures and the "infra-ordinary, " my approach pays attention to the highway as a material artefact. Who builds, maintains and manages it; who makes their life along it; what subcultures, lexicons and social behaviours can be read off it? Exploring the possibilities of creative non-fiction within the environmental humanities, the piece here unfolds as an exercise in psychogeography, or a deconstructed travelogue. While much travel writing about modern Cape Town describes a (motorised) journey from airport to city, here I reverse the gaze and proceed on foot from town to the airport along the hard shoulder of the N2. In doing so I try to understand the vexed relations between drivers and pedestrians in a divided city, and to conduct an "anthropology of the near" on the road reserve: perhaps the most visible but least contemplated part of the modern urban landscape.